2013
DOI: 10.2147/bctt.s50750
|View full text |Cite
|
Sign up to set email alerts
|

The incidence rate of female breast cancer in Saudi Arabia: an observational descriptive epidemiological analysis of data from Saudi Cancer Registry 2001–2008

Abstract: BackgroundThis study presents descriptive epidemiological data related to breast cancer cases diagnosed from 2001 to 2008 among Saudi women, including the frequency and percentage of cases, the crude incidence rate (CIR), and the age-standardized incidence rate (ASIR), adjusted by the region and year of diagnosis.MethodsThis is a retrospective descriptive epidemiological study of all Saudi female breast cancer cases from 2001 to 2008. The statistical analyses were conducted using descriptive statistics, a line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 11 publications
4
54
0
Order By: Relevance
“…The low percentage of local disease in our study might explain the high proportion of patients (84%) who received neoadjuvant chemotherapy. Similarly, stage I disease accounts for only a limited number of cases in other studies from our region, with the highest reported percentage being 23%, compared with 60% in developed countries 5,15. Young age at presentation and tumor size might significantly influence the design of national screening programs.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…The low percentage of local disease in our study might explain the high proportion of patients (84%) who received neoadjuvant chemotherapy. Similarly, stage I disease accounts for only a limited number of cases in other studies from our region, with the highest reported percentage being 23%, compared with 60% in developed countries 5,15. Young age at presentation and tumor size might significantly influence the design of national screening programs.…”
Section: Discussionmentioning
confidence: 45%
“…For example, the average patient age in Sweden is 60 years and Mexico 50 years, representing a 10-year difference 20. Our study population had a predominance of young patients (61.7% of patients were younger than 50 years), which is expected for this region; the average age in previous studies ranged between 40 and 45 years 3,5. Adami et al analyzed the relationship between age at diagnosis and relative survival in 57,068 Swedish women 21.…”
Section: Discussionmentioning
confidence: 59%
“…A similar study conducted by Alghamdi et al (21) between 2001 and 2008 reported a significant increase in female breast cancer, particularly among young women, in Saudi Arabia. The above study also specified the geographical locations of the prevailing disease, and identified that the Eastern region of Saudi Arabia presented a linear upward trend in the occurrence of breast cancer, compared with Southern areas of the country, including Jazan, Baha and Najran (21).…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with observations already (Shomaf et al, 2013;Zheng et al, 2014). An important point of exception was significant percentages of lymph node metastasis and LVI in both luminal subtypes, which is probably due to advanced BC stage at the time of presentation in all the subtypes in our population (Alghamdi et al, 2013). This fact necessitates more organized efforts to highlight the importance of expanding our public awareness regarding BC screening programs and early diagnosis.…”
Section: Discussionmentioning
confidence: 84%